Performance and antifouling evaluation of PSf/GO nanohybrid membrane on removing dye pollutant from batik wastewater - Tutuk Djoko Kusworo; Dita Aulia Azizah; Andri Cahyo Kumoro (Diponegoro University, 2023)
Membrane technology is the most widely used technology in the field of separation and purification of wastewater. Most of the problems that arise in the application of membrane technology are the high resistance of the membrane during the filtration process, so that fouling is easily formed in both the pores and the membrane surface. The incorporation of nanoparticles in the membrane matrix has been widely known as a method to improve membrane performance. In this study, we introduce the incorporation of graphene oxide (GO) advanced material nanoparticles in a polysulfone (PSf) membrane matrix as an effort to treat dye wastewater from the batik industry. The results of the SEM-EDX test showed the membrane smooth surface with larger pore and minimal defects indicating GO nanoparticles were well changed the polysulfone membrane matrix. In addition, an increase in oxygen content in the membrane matrix was also detected as a result of GO incorporation confirming the increased hydrophilicity of the polysulfone membrane. This is also supported by data on increasing water uptake and decreasing contact angle of PSf/GO membranes compared to native PSf. Evaluation of membrane performance showed that the incorporation of GO in the PSf matrix produced permeate with higher quantity and quality than the native PSf membrane. Quantitative analysis of fouling behavior also shows that the incorporation of GO as much as 2 wt-% has succeeded in increasing flux recovery ratio and reducing the PSf membrane resistance which reflects the tendency to form fouling is also getting lower. This membrane material has good prospects in the future as the first step in processing dye wastewater from various industries, especially the batik industry.